2013
DOI: 10.1259/dmfr.20120343
|View full text |Cite
|
Sign up to set email alerts
|

Using GafChromic film to estimate the effective dose from dental cone beam CT and panoramic radiography

Abstract: Objectives: To demonstrate the feasibility of GafChromic ® XR-QA2 (ISP Corp., Wayne, NJ) as a dosemeter when performing measurements of the effective dose from three cone beam CT (CBCT) units and to compare the doses from examinations of three common dental clinical situations. A second aim was to compare the radiation doses for three digital panoramic units with the doses for the CBCT units. Methods: The CBCT units used were Veraviewepocs 3De ® (J Morita MFG Corp., Kyoto, Japan), ProMax ® 3D (Planmeca, Helsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The dose of FOVs of ,10 cm was higher for examination of the lower jaw than for the upper jaw 23,30 and for examinations with the FOV positioned on the posterior part of the lower jaw than for the anterior part of the upper jaw. 14,38,45 The effective dose was reduced by 43% when 0.4-mm copper filtration was added in examinations with FOV heights 9 and 18 cm. 18 Effective dose was related to image quality in six studies (Table 2) expressed as objective image quality 21,32,39,40 or subjective image quality.…”
Section: Study Selectionmentioning
confidence: 99%
“…The dose of FOVs of ,10 cm was higher for examination of the lower jaw than for the upper jaw 23,30 and for examinations with the FOV positioned on the posterior part of the lower jaw than for the anterior part of the upper jaw. 14,38,45 The effective dose was reduced by 43% when 0.4-mm copper filtration was added in examinations with FOV heights 9 and 18 cm. 18 Effective dose was related to image quality in six studies (Table 2) expressed as objective image quality 21,32,39,40 or subjective image quality.…”
Section: Study Selectionmentioning
confidence: 99%
“…For the range of energy selected by the authors, the dependence on energy remained below 10%. Al-Okshi et al (2013) found virtually coincident dose-response curves when testing the Gafchromic s XR-QA2 film for 60 kV, 80 kV and 120 kV beams, which suggests weak dependence on energy within the selected energy range.…”
Section: The Cdtn Multipurpose Instrumentmentioning
confidence: 87%
“…Especially if small fields of view are used for CBCT, radiation exposure is significantly reduced. However, this exposure to radiation as well as the costs are still significantly higher when compared to those of conventional dental imaging [1922]. For diagnosis and general preoperative planning, both PAN and CBCT are described to be useful and important diagnostic tools [11, 23, 24].…”
Section: Introductionmentioning
confidence: 99%